2014
DOI: 10.1016/j.humpath.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of Yes-associated protein expression in the diagnosis of persistent neonatal cholestatic liver disease

Abstract: Although physiologic jaundice of neonates is common, persistent neonatal cholestasis is life-threatening and has multiple etiologies. Among these etiologies, biliary atresia (BA) requires rapid diagnosis and treatment. In diagnosing BA, the surgical pathologist must recognize subtle histologic changes, often with only a small core liver biopsy. To aid in the differential diagnosis of neonatal cholestasis, we investigated Yes-associated protein (YAP), a regulator of organ size and bile duct development. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 33 publications
7
34
0
Order By: Relevance
“…Consistent with previous reports, JNK signaling was not activated in hepatocytes in BDL-induced cholestasis [46]. Furthermore, YAP was reported to be involved in cholestasis-related liver fibrosis and liver cancer progression, and served as a classical upstream regulator of CTGF/CCN2 in mammalian cells [29,30]. Thus, we investigated whether BAs regulate CTGF/CCN2 levels through YAP and found that TC increased YAP levels in hepatocytes.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previous reports, JNK signaling was not activated in hepatocytes in BDL-induced cholestasis [46]. Furthermore, YAP was reported to be involved in cholestasis-related liver fibrosis and liver cancer progression, and served as a classical upstream regulator of CTGF/CCN2 in mammalian cells [29,30]. Thus, we investigated whether BAs regulate CTGF/CCN2 levels through YAP and found that TC increased YAP levels in hepatocytes.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 86%
“…TGF-β can induce CTGF/CCN2 expression in a Smaddependent manner in hepatocytes [26], whereas it regulates the expression of CTGF/CCN2 through Smad-independent signaling in hepatic progenitor cells [27]. CTGF/CCN2 also acts as a downstream gene of Yes-associated protein (YAP) [28], which has been reported to be involved in cholestasis [29,30]. Moreover, enhanced expression of CTGF/CCN2 was observed in liver tissues of cholestatic patients [31].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have demonstrated a close association between cholestasis and Hippo signaling (133)(134)(135). Cholestasis is usually caused by the disruption of enterohepatic circulation and overload of bile acids, which results in diseases such as primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC).…”
Section: The Hippo Pathway In Liver Cancermentioning
confidence: 99%
“…Additionally, VP treatment reduced cell proliferation more pronouncedly in HuCCT1 cholangiocarcinoma cell line than it did to normal cholangiocyte cell line H69, suggesting the potential of VP in treating cholangiocarcinoma [62].…”
Section: Disrupting Yap-tead Interactionmentioning
confidence: 90%
“…Elevated nuclear YAP expression was found in ductular reactions of primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC) [26] as well as in bile duct epithelium of neonates with biliary atresia [62]. In cholestatic livers of young patients, hepatocytes also display robust YAP staining [63].…”
Section: Yap and Other Liver Diseasesmentioning
confidence: 99%